New paradigms for organ allocation and distribution in liver transplantation. Issue 3 (May 2018) - Kalra, Avash; Biggins, Scott W.
Abstract : Purpose of review: The 'Final Rule, ' issued by the Health Resources and Service Administration in 2000, mandated that liver allocation policy should be based on disease severity and probability of death, and – among other factors – should be independent of a candidate's residence or listing. As a result, the Organ Procurement Transplantation Network/United Network for Organ Sharing (UNOS) has explored policy changes addressing geographic disparities without compromising outcomes. Recent findings: Major paradigm shifts are underway in U.S. liver allocation policy. New hepatocellular carcinoma exception policy incorporates tumor characteristics associated with posttransplantation outcomes, whereas a National Liver Review Board will promote a standardized process for awarding exception points. Meanwhile, following extensive debate, new allocation policy aims to reduce geographic disparity by broadening sharing to the UNOS region and 150-mile circle around the donor hospital for liver transplant candidates with a calculated model for end-stage liver disease score at least 32. Unnecessary organ travel will be reduced by granting 3 'proximity points' to candidates within the same donation service area (DSA) as a liver donor or within 150 nautical miles of the donor hospital, regardless of DSA or UNOS region. Summary: This review provides an evaluation of major policy changes in liver allocation from 2016 to 2018.